A educação ambiental crítica no Brasil : as questões de gênero e da diversidade sexual, entre (in)visibilidade e dialogia - Silva, Victor Nathan Fontes (2018)
This research’s object of study consists of the area occupied by gender and sexual diversity’s issues on Brazilian’s critical environmental education knowledge production. The circularities, ambiguities, (in) visibilities and dialogues related to gender and sexual diversity, found in scientific production on critical environmental education, were analysed from a cultural, social and political perspective. This research’s theoretical-methodological basis is John Thompson’s depth hermeneutics. The research’s mode encompasses exploratory research from theoretical research. Thompsian hermeneutics was applied in the analysis of articles and books by Brazilian authors in the field of critical environmental education, by means of the following procedures: (a) identification of means of production, communication and dissemination of symbolic forms of produced knowledge; (b) analysis of textual communicative messages construction; (c) characterization of the communicated messages’ reception and appropriation; (d) daily appropriation of cultural products (communicated symbolic forms) within specific fiels of social life, whether in a group of people in institutions or social collectives, specifically scientific articles’ production, Lattes’ records and circulation in academic and non-college circulation.